AN ANALYSIS OF SPONTANEOUS ENGLISH CONVERSATIONS AMONG SECOND SEMESTER STUDENTS OF THE ENGLISH EDUCATION DEPARTMENT OF SAN PEDRO UNIVERSITY IN ACADEMIC YEAR 2017/2018 - Yohanes Paulus Silli Bataona; Tans Feliks; Agustinus Semiun (IJER - INDONESIAN JOURNAL OF EDUCATIONAL REVIEW, 2018)
The aims of this study are describing the topics conversed by the second semester students of the English education department of San Pedro University; analyzing what are students’ conversations for; analyzing how students converse with their friends; and analyzing what are students’ strengths and weaknesses in English conversations. To reach these objectives, this research was designed in a descriptive qualitative study. All the data were obtained through observation, documentation (recordings), and interview. The data was collected and analyzed through descriptive approach. And after analyzing the data on the basis of research questions dealing with English conversations among the students, the researcher finds that there are different topics that conversed by the students, and all those topics are very contextual with the real life of students; or in other words, the topics present what students’ lives are. The students did English conversations in order to develop their ability to speak English confidently and pronounce English words correctly; encourage them to use appropriate grammar and vocabulary in English speaking; help them to produce and organize their ideas logically; and develop their communication competence such as oral presentation and story-telling. There are several findings deal with how do students converse with their friends: they do their conversations with big motivation; they begin their conversations with good starting point; they present good turn taking in their conversations; they present good cultural act in their conversations; they conduct their conversations with low accuracy; they conduct their conversations with low fluency; they present cohesion and coherence in their conversations; and they end their conversations with good closing point. And in conducting English conversations, there are strengths and weaknesses. The strengths found in students’ conversations are: students have big motivation in doing English conversations, using very simple vocabularies in their conversations; conversations run spontaneously and naturally; more reactive or responsive in doing conversations; creating good use of conjunctions and determiners; and giving good extended answers to the questions appeared in conversations. While the weaknesses found in students’ conversations are: students are still poor in vocabulary, still weak in using proper grammar, pronunciations and intonations are not so good affected by local language so much.